2021
DOI: 10.17533/udea.ikala.v26n3a03
|View full text |Cite
|
Sign up to set email alerts
|

"And My Screen Wouldn't Share": Student-Teachers' Perceptions of ICT in Online Teaching Practice and Online Teaching

Abstract: The sudden switch to online teaching enforced by the covid-19 pandemic has impacted teacher education at universities, particularly micro-teachings and teaching practice, as technology has become an inherent part of these processes. The growing body of literature on online teaching and teacher education during lockdown conditions mainly addresses challenges in teacher education and educator perceptions. However, very few studies deal with the perceptions of student- teachers. To fill this gap, a group of teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Si bien el análisis de datos no arrojó diferencias significativas, un análisis más descriptivo de las respuestas a ambos tipos de preguntas en los dos cuestionarios mostró una mejora en algunas dimensiones, especialmente en el manejo del aula y en lo que ello implica, como motivar a los alumnos a participar en discusiones, aunque este aumento de la motivación y la participación pudo ser causado por el propio uso de las nuevas tecnologías que suponen sí mismas un elemento motivador (Torrado Cespón, 2021). En el PREC, esta dimensión obtuvo las puntuaciones más bajas, debido a que los profesores se enfrentaban a una situación totalmente desconocida y nueva y no tenían ni formación ni experiencia para asumirla, lo que coincide con estudios previos sobre enseñanza en línea (Barbour y Harrison, 2016;Wu, 2016) concluyendo que uno de los aspectos que mostraba mayor dificultad para los profesores era mantener las relaciones con y entre los alumnos en las clases virtuales (Fortová et al, 2021). No obstante, tras más de un año de uso de plataformas digitales y habiendo recibido algo de formación, los profesores se mostraron más seguros y puntuaron mejor su percepción sobre llevar a cabo las distintas responsabilidades dentro del manejo del aula.…”
Section: Discussionunclassified
“…Si bien el análisis de datos no arrojó diferencias significativas, un análisis más descriptivo de las respuestas a ambos tipos de preguntas en los dos cuestionarios mostró una mejora en algunas dimensiones, especialmente en el manejo del aula y en lo que ello implica, como motivar a los alumnos a participar en discusiones, aunque este aumento de la motivación y la participación pudo ser causado por el propio uso de las nuevas tecnologías que suponen sí mismas un elemento motivador (Torrado Cespón, 2021). En el PREC, esta dimensión obtuvo las puntuaciones más bajas, debido a que los profesores se enfrentaban a una situación totalmente desconocida y nueva y no tenían ni formación ni experiencia para asumirla, lo que coincide con estudios previos sobre enseñanza en línea (Barbour y Harrison, 2016;Wu, 2016) concluyendo que uno de los aspectos que mostraba mayor dificultad para los profesores era mantener las relaciones con y entre los alumnos en las clases virtuales (Fortová et al, 2021). No obstante, tras más de un año de uso de plataformas digitales y habiendo recibido algo de formación, los profesores se mostraron más seguros y puntuaron mejor su percepción sobre llevar a cabo las distintas responsabilidades dentro del manejo del aula.…”
Section: Discussionunclassified
“…Additionally, investigations on students' and teachers' experiences revealed positive attitudes toward online devices (Akram et al 2021;Rossettini et al 2021). Students seemed to have normalised the use of teaching platforms (Fořtová, Sedláčková, and Tůma 2021), and although most of them still preferred a combination of in-person and online activities rather than a fully online course (Ashkanani et al 2022), the demand for online courses is likely to increase in the future (McKenzie 2021).…”
Section: Online Teaching and Emergency Online Teaching In Higher Educ...mentioning
confidence: 99%
“…These elements are then related to students' active and autonomous learning and class interaction, highlighting the ongoing need for teacher training on remote teaching and for reflecting on teacher roles to ensure empathy, communication, and assessment throughout the lessons. Fořtová et al (2021) followed a qualitative analysis to examine the teaching experience of 63 teachers in a master's program in the Czech Republic. Analysis of their post-lesson reflections revealed that the participants found the online environment limiting and described it as an unauthentic learning experience.…”
Section: Challenges During the Pandemicmentioning
confidence: 99%
“…This is particularly relevant to the many challenges school administrators, parents, teachers, and students faced during the COVID-19 lockdown (Madianou, 2020). Research has looked into teachers' responses to the challenges of remote instruction (Corrales & Rey-Paba, 2021) and their effective use of digital technologies (Fořtová et al, 2021); however, few studies have examined how preservice teachers coped with these particular teaching circumstances. Our study addresses these concerns and aims to contribute to the calls for exploring TBLT as a tool within the myriad practices and knowledge practitioners hold, especially amidst current vulnerable times.…”
Section: Introductionmentioning
confidence: 99%